2015
DOI: 10.1093/jpepsy/jsv079
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Translation: Identifying Behavioral Health Disparities in Pediatric Primary Care

Abstract: Although care within a medical home increases parental satisfaction with health care services and improves health care utilization, significant racial/ethnic and language disparities persist in health care settings. Integrated, team-based approaches can decrease health disparities. The current study examines medical records of 2,353 youth who received a behavioral health consultation in an urban, residency training pediatric primary care clinic. A three-phase, mixed-method approach was used to examine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…However, Spanish-speaking clinicians were available in the YPIC study, extensive training on cultural factors aimed at enhancing clinician cultural sensitivity was provided, and telephone outreach was used when patients were unable to attend the clinics. Our findings, therefore, underscore the challenges and need for novel strategies to identify and address other factors that may be deterring service use among less acculturated families (Becker Herbst, Margolis, Millar, Muther, & Talmi, 2016).…”
Section: Discussionmentioning
confidence: 70%
“…However, Spanish-speaking clinicians were available in the YPIC study, extensive training on cultural factors aimed at enhancing clinician cultural sensitivity was provided, and telephone outreach was used when patients were unable to attend the clinics. Our findings, therefore, underscore the challenges and need for novel strategies to identify and address other factors that may be deterring service use among less acculturated families (Becker Herbst, Margolis, Millar, Muther, & Talmi, 2016).…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, research has shown that integrated behavioral health in primary care helps reduce health disparities in ethnically and racially diverse populations, especially in the areas of identification of mental health or developmental concerns and the connection of families to necessary external services (Becker Herbst et al, 2016). This literature supports the need for additional research examining differences in how various ethnic/racial groups access, use, and are impacted by integrated behavioral health services.…”
mentioning
confidence: 72%
“…Additionally, pediatric psychologists in integrated practice can delineate the specific requirements necessary to build workforce capacity to adequately meet the demand for behavioral health in pediatric primary care. Recognizing the importance and success of integrated behavioral health in primary care, increasing attention has been paid to building a competent workforce that is able to practice effectively as a part of the multidisciplinary primary care medical team Becker Herbst, Margolis, Millar, Muther, & Talmi, 2016) and meet the complex needs of diverse populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Ethnic minority youth and youth in poverty are at a higher risk of mental health problems, yet are even less likely to receive behavioral health treatment than youth overall. 1,[3][4][5] In recent decades, the placement of behavioral health providers (eg, psychologists, psychiatrists, counselors, and clinical social workers) within the primary care setting has been explored as a method of increasing access to pediatric mental and behavioral health services. 6,7 The American Academy of Pediatrics recommends 12 wellchild visits to the primary care provider (PCP) by the age of 3 years, followed by annual visits until age 21 years.…”
Section: Introductionmentioning
confidence: 99%